CuS enhanced super-amphiphobic photo-thermal anti-icing coating as well as preparation method and application thereof

Through the organic combination of CuS and Fe3O4, CuS-Fe3O4 composite material is formed, which solves the problems of poor stability of Fe3O4 and photothermal effect saturation, and achieves efficient anti-icing and good stability of the ultra-double light-sparse thermal anti-ice coating.

CN119875402APending Publication Date: 2025-04-25WUHAN SUNENG NEW MATERIAL CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510053299.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-14
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

In the prior art, the magnetic nanoparticle Fe3O4 is easily oxidized in air, has poor stability, and the photothermal effect shows saturation, which limits its application in the photothermal field.

Method used

By organically combining CuS with Fe3O4, CuS-Fe3O4 composite material is formed, and its effective composite is achieved in the ultra-double-sparing coating system, and a photothermal ultra-double-sparing anti-ice coating is constructed by combining the resin base layer.

Benefits of technology

It has achieved excellent ultra-double-sparing properties, photothermal effect and stability, significantly improved the application potential of photothermal materials, can effectively prevent deicing in low temperature and high humidity environments, and has good self-cleaning and durability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005240612920000131
    Figure BDA0005240612920000131
  • Figure BDA0005240612920000141
    Figure BDA0005240612920000141
  • Figure HDA0005240612930000011
    Figure HDA0005240612930000011
Patent Text Reader

Abstract

The invention discloses a CuS enhanced super-amphiphobic photo-thermal anti-icing coating, which comprises a photo-thermal composite super-amphiphobic surface layer and a resin bottom layer, and finish paint adopted by the photo-thermal composite super-amphiphobic surface layer is prepared from the following components in parts by weight: 0.06 to 0.08 part of CuS-Fe3O4 composite material, 0.8 to 2 parts of hydrolyzable silicon source, 4 to 6 parts of alcohol solvent, 0.2 to 0.5 part of alkali liquor, 0.014 to 0.02 part of fluorocarbon and 0.8 to 2 parts of acid liquor. And 0.8 to 2 parts of silane low surface energy substances. According to the method, CuS and Fe3O4 are organically combined and effectively compounded in a super-amphiphobic coating system, and the obtained anti-icing coating has excellent super-amphiphobic performance, photothermal effect, stability and the like; and the related preparation process is simple, convenient and feasible, low in energy consumption, capable of realizing large-scale production and suitable for popularization and application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of functional coatings, and in particular relates to a CuS enhanced super-amphiphobic photothermal anti-icing coating and a preparation method and application thereof. Background Art

[0002] Traditional deicing technologies include thermal deicing, mechanical deicing, liquid deicing and other methods, but they usually have disadvantages such as high power consumption, low deicing efficiency, low safety, and environmental pollution. The micro-nanostructure of super-hydrophobic surfaces makes them extremely valuable in self-cleaning, anti-icing, anti-corrosion and oil-water separation, and research in the field of deicing has made great progress; however, the deicing performance of traditional super-hydrophobic surfaces is not stable, especially under low temperature and high humidity conditions, the deicing effect is significantly reduced.

[0003] Photothermal materials can convert light energy into heat energy, and using solar energy, a clean renewable energy source, for deicing is a safe and pollution-free deicing method. In recent years, the combination of photothermal materials and super-hydrophobic materials to manufacture photothermal super-hydrophobic surfaces and their application in the field of deicing has received widespread attention.

[0004] According to the different types of photothermal nanoparticles added to the material, the photothermal materials used for photothermal super-hydrophobic surfaces mainly include iron oxide, titanium nitride, silicon carbide, carbon nanotubes, graphene, biochar, candle ash, etc. As an excellent photothermal agent, Fe3O4 has good photothermal and magnetic properties and is often used as a magnetic adsorbent in biomedical fields such as molecular imaging and disease diagnosis, as well as in the field of photocatalytic degradation. However, since magnetic nanoparticles are easily oxidized in the air, have the characteristics of high specific area and strong aggregation tendency, they have poor stability in practical applications, and are usually difficult to use in combination with other types of photothermal materials, which seriously limits their promotion and application. In addition, the photothermal effect of Fe3O4 shows obvious saturation, and its photothermal warming effect cannot be further improved after reaching a certain amount of addition, which weakens its application in the photothermal field. Further improving the stability of magnetic nanoparticles, maximizing the photothermal performance of Fe3O4, and improving the limitations of Fe3O4 in practical applications are currently urgent problems to be solved. Summary of the invention

[0005] The main purpose of the present invention is to address the deficiencies in the prior art and provide a CuS-enhanced Fe3O4 photothermal super-amphiphobic anti-icing coating, which organically combines CuS and Fe3O4 and realizes their effective compounding in a super-amphiphobic coating system, while taking into account excellent super-amphiphobic performance, photothermal effect and stability; and the preparation process involved is simple and easy, has low energy consumption, can be mass-produced, and is suitable for promotion and application.

[0006] To achieve the above object, the technical solution adopted by the present invention is:

[0007] A CuS enhanced super-amphiphobic photothermal anti-icing coating comprises a photothermal composite super-amphiphobic surface layer and a resin bottom layer. In the topcoat used for the photothermal composite super-amphiphobic surface layer, the components and their weight proportions include: 0.06-0.08 parts of CuS-Fe3O4 composite material, 0.8-2 parts of hydrolyzable silicon source, 4-6 parts of alcohol solvent, 0.2-0.5 parts of alkali solution, 0.014-0.02 parts of fluorocarbon, 0.8-2 parts of acid solution, and 0.8-2 parts of silane low surface energy material.

[0008] In the above scheme, the CuS-Fe3O4 composite material is firstly obtained by surface-activating Fe3O4 particles with a ligand, and then sequentially adding the sulphur source solution and the copper salt solution and stirring them.

[0009] Furthermore, the specific preparation steps of the CuS-Fe3O4 composite material include:

[0010] 1) Adding Fe3O4 particles to the ligand solution and stirring the solution to activate the surface of the Fe3O4 particles to obtain a Fe3O4-ligand mixed solution;

[0011] 2) adding the obtained Fe3O4-ligand mixed solution into the sulfur source solution and stirring evenly to obtain a S-Fe3O4-ligand precursor solution;

[0012] 3) Under stirring conditions, the obtained S-Fe3O4-ligand precursor solution is added dropwise to the copper salt solution, and stirred at room temperature to obtain a CuS-Fe3O4-based black-green solution, which is washed and centrifuged to obtain a CuS-Fe3O4 composite material.

[0013] In the above scheme, the ligand can be selected from one of thioglycolic acid (TGA), 3-mercaptopropionic acid (MPA), glutathione (reduced GSH), etc.

[0014] In the above scheme, the particle size of the Fe3O4 particles is 400-500nm.

[0015] In the above scheme, in the Fe3O4-ligand mixed solution, the ligand concentration is 0.1-0.5 mol / L, and the concentration of Fe3O4 particles is 0.08-0.16 g / mL.

[0016] In the above scheme, the stirring treatment time in step 1) is 15 to 30 minutes.

[0017] In the above scheme, the sulfur source can be selected from one of sodium sulfide (Na2S), thiourea (NH4)2S, etc.

[0018] In the above scheme, the concentration of the sulfur source solution is 0.24-0.4 mol / L.

[0019] In the above scheme, in the S-Fe3O4-ligand precursor solution, the molar ratio of the introduced ligand, S source and Fe3O4 is (0.5-1):(1-2):0.86.

[0020] Furthermore, in the S-Fe3O4-ligand precursor solution, the concentration of Fe3O4 is 0.04-0.05 g / mL.

[0021] In the above scheme, the copper salt can be selected from one or more of copper nitrate, copper acetate, copper chloride and the like.

[0022] In the above scheme, the concentration of the copper salt solution is 0.03-0.05 mol / L.

[0023] In the above scheme, the droplet acceleration rate of the S-Fe3O4-ligand precursor solution is 100 to 120 drops / min.

[0024] In the above scheme, the stirring time at room temperature in step 3) is 2 to 4 hours.

[0025] In the above scheme, the alcohol solvent can be selected from one of ethanol, methanol, isopropanol and the like.

[0026] In the above scheme, the alkali solution can be selected from one of NaOH aqueous solution, ammonia water, KOH solution, etc., wherein the concentration of NaOH aqueous solution is 1-1.8 mol / L, the concentration of ammonia water is 25-28 wt%, and the concentration of KOH aqueous solution is 1-1.8 mol / L.

[0027] In the above scheme, the hydrolyzable silicon source can be selected from at least one of tetraethyl orthosilicate, methyltrimethoxysilane, ethyltriethoxysilane, tetramethylsiloxane, sodium silicate and the like.

[0028] In the above scheme, the fluorocarbon compound can be selected from perfluorodecyltrimethoxysilane, perfluorodecyltriethoxysilane, perfluorooctyltrimethoxysilane, perfluorooctyltriethoxysilane and the like.

[0029] Furthermore, the fluorocarbon is introduced in the form of a fluorocarbon precursor solution, specifically prepared using an alcohol solvent, wherein the concentration of the fluorocarbon is 4-6 vol%.

[0030] Preferably, the fluorocarbon compound can be perfluorodecyltrimethoxysilane (PFDTMS); the alcohol solvent can be ethanol or the like.

[0031] In the above scheme, the acid solution can be selected from one of H2SO4 solution, HCl solution, HNO3 solution, etc., and its concentration is 0.65-1.3 mol / L.

[0032] Preferably, the concentration of H2SO4 solution is 0.65-1 mol / L, the concentration of HCl solution is 0.65-1 mol / L, and the concentration of HNO3 solution is 1-1.3 mol / L.

[0033] In the above scheme, the silane-based low surface energy material can be selected from one of hexamethyldisilazane (HMDS), methyltriethoxysilane (MTES), hexadecyltrimethoxysilane (HDTMS) and the like.

[0034] In the above scheme, the components and their weight proportions in the primer used in the resin bottom layer include: 145-180 parts of resin matrix, 10-20 parts of powder filler, 4-5 parts of curing agent, 1.1-4 parts of silane coupling agent, and 240-300 parts of organic solvent.

[0035] In the above scheme, the resin matrix can be selected from one or more of alkyd resin, epoxy resin, polypropylene resin, polyurethane, silicone resin, fluorocarbon resin, phenolic resin, urea-formaldehyde resin, and hydroxy acrylic resin.

[0036] Preferably, the resin matrix is ​​formed by mixing hydroxy acrylic resin, fluorocarbon resin, alkyd resin and polypropylene resin in a mass ratio of (80-100):(15-20):(40-45):(10-15).

[0037] In the above scheme, the silane coupling agent can be selected from one or more of kh550, kh560, kh570 and the like.

[0038] In the above scheme, the powder filler can be selected from one or more of nylon powder, talcum powder, mica powder, quartz powder, etc., and its particle size is 200-800 meshes.

[0039] In the above scheme, the curing agent can be selected from one or more of isocyanate curing agents, ethylenediamine, m-phenylenediamine, phthalic acid, tetraisopropyl titanium and the like.

[0040] The above-mentioned method for preparing a CuS enhanced super-amphiphobic photothermal anti-icing coating comprises the following steps:

[0041] (1) Under stirring conditions, a CuS-Fe3O4 composite material is added to an alcohol solvent, and then an alkali solution and a hydrolyzable silicon source are sequentially added to the obtained mixed solution for hydrolysis reaction; after the hydrolysis is sufficient, a fluorocarbon-based precursor liquid is added to the obtained reaction system to perform a first stirring reaction, and then an acid solution is added to perform a second stirring reaction, and then a silane-based low surface energy material is added for stirring treatment to obtain a photothermal composite super-amphiphobic topcoat;

[0042] (2) adding a resin matrix, a silane coupling agent, a powder filler, and a curing agent to an organic solvent in sequence under stirring, and stirring the mixture sufficiently to obtain a resin primer;

[0043] (3) First spray the obtained resin primer on the surface of the substrate, and after the surface is dried, spray the obtained photothermal composite super-amphiphobic topcoat, and dry it to obtain the CuS enhanced super-amphiphobic photothermal anti-icing coating.

[0044] In the above scheme, the hydrolysis reaction time is 12 to 24 hours.

[0045] In the above scheme, in step (1), the first stirring reaction time is 30 to 45 minutes; the second stirring reaction time is 15 to 20 minutes.

[0046] In the above scheme, in step (1), the stirring treatment time is 10 to 12 hours.

[0047] In the above scheme, the sufficient stirring time in step (2) is 12 to 24 hours.

[0048] In the above scheme, the reaction temperature in all reaction steps is room temperature.

[0049] The CuS enhanced photothermal super-amphiphobic anti-icing coating prepared according to the above scheme has excellent super-hydrophobicity, super-oleophobicity, near-infrared plasma resonance performance, high photothermal conversion efficiency and long-term durability, water contact angle (CA)>158°, water rolling angle (SA)<2°, oil contact angle (CA)>155°, oil rolling angle (SA)<2°. It is applied in the field of photothermal anti-icing and has great application potential.

[0050] The principle of the present invention is:

[0051] The present invention first adds Fe3O4 particles into a ligand solution for surface activation, forms coordination bonds on the surface of the Fe3O4 particles and enhances the hydrophilicity of the Fe3O4 particles, thereby promoting the stable dispersion of Fe3O4 powder in an aqueous solution; then introduces the particles into a reaction system of a copper salt and a sulfur source for reaction and compounding to obtain CuS-Fe3O4 composite particles; then introduces the particles into a silicon source hydrolysis system and adopts an in-situ synthesis method to prepare a CuS-Fe3O4@SiO2 dispersion with good dispersibility; then introduces long-chain carbon fluoride molecules, an acid solution and a silane-based low-surface-energy substance to chemically modify the surface of the CuS-Fe3O4@SiO2 composite particles to obtain a super-amphiphobic topcoat; and finally, in combination with a resin primer, a super-amphiphobic photothermal anti-icing coating containing the composite particles is constructed on the surface of a substrate.

[0052] Under no-light conditions, the combination of low surface energy and special rough structure can effectively reduce the surface wettability of the obtained coating, greatly reducing the amount of water hanging before freezing; under light conditions, the synergistic enhanced photothermal effect of CuS-Fe3O4 composite particles enables the obtained coating to continuously absorb sunlight, converting light energy into heat energy, making it difficult for water droplets to reach supercooled temperatures and freeze, thereby significantly delaying the freezing time of water droplets; the frozen coating surface can also quickly de-ice under light conditions. In addition, the coating of the present invention not only has good super-amphiphobic anti-icing performance, but also can effectively resist impurities such as dust, and has good self-cleaning properties, weather resistance and durability.

[0053] Compared with the prior art, the present invention has the following beneficial effects:

[0054] 1. The photothermal anti-icing coating of the present invention exhibits excellent super-hydrophobic and super-oleophobic properties, and can also exhibit good self-cleaning properties, effectively resisting the erosion of dust and bacteria in the air, and ensuring the super-amphiphobic durability of the coating;

[0055] 2. The present invention successfully compounds CuS and Fe3O4 to form a new structure, effectively ensuring and exerting the synergistic enhanced photothermal effect of CuS on Fe3O4, and significantly improving the photothermal absorption performance of the resulting composite photothermal material; the CuS-Fe3O4@SiO2 photothermal super-amphiphobic topcoat prepared using the CuS-Fe3O4 composite material can effectively ensure the stability of Fe3O4 in use.

[0056] 3. The photothermal anti-icing coating of the present invention adopts a double-layer coating method of primer and topcoat, which can effectively improve the adhesion of the super-amphiphobic topcoat: the topcoat and primer are used in combination with nano- and micro-materials of different particle sizes to form a complex particle size gradient, providing a special rough structure, which is beneficial to improving the super-amphiphobicity of the coating and extending its service life; so that it can have good adhesion on glass substrates, stainless steel, aluminum alloys and other metal materials;

[0057] 4. The photothermal anti-icing coating of the present invention exhibits a very excellent delayed icing effect: under no-light conditions, water droplets are not easy to stay on the surface of the substrate, and the attached water droplets can also quickly roll off the surface under the action of external forces such as tilting or wind blowing; at the same time, due to the small contact area between the condensed water droplets and the substrate surface and the inhibition of heat transfer, the freezing time of the condensed water droplets on the surface of the super-amphiphobic material is extended; and under light conditions, the photothermal composite particles contained in the coating continuously absorb sunlight and convert light energy into heat energy. Even if the ambient temperature is -20°C, the surface temperature of the coating can be at least 10°C higher than the ambient temperature, making it difficult for the connection between the water droplets and the coating surface to reach a supercooled temperature and freeze, thereby significantly delaying the freezing time of the water droplets;

[0058] 5. The coating provided by the present invention can effectively reduce the amount of ice: the coating has low surface energy and a special rough structure, which greatly reduces the actual contact area between the droplets and the surface. The water droplets can easily roll and slide under the action of natural external forces, thereby reducing the amount of water hanging before freezing; in addition, under light, the frozen ice layer can quickly melt at the connection with the coating surface, and the melted ice layer will fall off immediately based on the super amphiphobicity of the coating. BRIEF DESCRIPTION OF THE DRAWINGS

[0059] Figure 1 This is the morphology of the photothermal anti-icing coating obtained in Example 1.

[0060] Figure 2 Graph showing the contact angles of the photothermal anti-icing coating obtained in Example 1, where (a) is the water contact angle and (b) is the oil contact angle.

[0061] Figure 3 This is the TEM image of the photothermal anti-icing coating obtained in Example 1.

[0062] Figure 4 These are SEM images of the coating obtained in Example 1, where (a) shows that the entire coating surface presents a dense protrusion-like rough structure, (b) is a morphology image of a single protrusion at high resolution, and (c) is a layered rough structure presented on the surface of a single protrusion.

[0063] Figure 5 This is the morphology of the photothermal anti-icing coating obtained in Example 2.

[0064] Figure 6 Graph showing the contact angles of the photothermal anti-icing coating obtained in Example 1, where (a) is the water contact angle and (b) is the oil contact angle.

[0065] Figure 7 This is a comparison chart of the absorption curves of the photothermal anti-icing coatings obtained in Examples 1 and 2 and a blank glass substrate.

[0066] Figure 8 The photothermal anti-icing coating obtained in Example 1 and a blank glass substrate, a super-amphiphobic SiO2 coating (Comparative Example 1), and a Fe3O4-SiO2 coating without CuS reinforcement (Comparative Example 2) were subjected to a light intensity of 1 kW / m 2 Below is a comparison of the surface temperature changes over time.

[0067] Fig. 9 The photothermal anti-icing coating obtained in Example 1 and the coatings obtained in Comparative Examples 1 to 4 at an ambient temperature of -30°C under no light and a light intensity of 1 kW / m 2 Comparison of the delayed freezing time of methylene blue droplets under xenon lamp irradiation.

[0068] Fig.10The photothermal anti-icing coating obtained in Example 1 and the coatings obtained in Comparative Examples 1 to 4 at an ambient temperature of -15°C under a light intensity of 1 kW / m 2 Comparison of ice removal (icicle) time under xenon lamp irradiation.

[0069] Fig.11 The photothermal anti-icing coating obtained in Example 1 and the coatings obtained in Comparative Examples 1 to 4 at an ambient temperature of -20°C under a light intensity of 1 kW / m 2 Comparison of ice melting (smoothie) time under xenon lamp irradiation. DETAILED DESCRIPTION

[0070] The applicant will further explain the present invention in detail below in conjunction with specific embodiments so that those skilled in the art can more clearly understand the present invention. However, the following content should not be construed as limiting the scope of protection of the claims of the present invention.

[0071] The chemical reagents and solvents used in the examples are all analytically pure. The stirring is carried out using a magnetic stirrer.

[0072] Example 1

[0073] A CuS enhanced super-amphiphobic photothermal anti-icing coating, the preparation method of which comprises the following steps:

[0074] (1) Preparation of CuS-Fe3O4 composite materials:

[0075] Weigh 0.20 g Cu(Ac)2·H2O (1 mmol) and dissolve it in 25 mL deionized water to obtain a light blue Cu 2+ Precursor solution (0.04 M);

[0076] Weigh 2.5 mL of TGA (thioglycolic acid) solution (0.4 M, solvent is water) and add 0.2 g of commercially available Fe3O4 nanoparticles (particle size is 400-500 nm) into the TGA solution, and stir for 30 min to fully activate the surface of the Fe3O4 particles in the TGA solution;

[0077] Weigh 0.48 g Na2S·9H2O (2 mmol, S:Cu=2:1) ​​and dissolve it in 6.25 mL deionized water to obtain a colorless and transparent sulfur source solution (0.32 M), and add the obtained TGA solution to the sulfur source solution and stir evenly to obtain a S-Fe3O4-TGA precursor solution;

[0078] Under stirring conditions, the obtained S-Fe3O4-TGA precursor solution was slowly added to the obtained Cu at a drop rate of 100 drops / min. 2+Precursor solution; after stirring at room temperature for 4 hours, a CuS-Fe3O4 black-green solution was obtained, which was washed with water and then centrifuged with ethanol to obtain a CuS-Fe3O4 precipitate;

[0079] (2) Under stirring, add 0.4 g of CuS-Fe3O4 precipitate obtained in step (1) to 25 mL of ethanol solvent and stir for 10 min, then add 1.5 mL of NaOH solution (1.8 mol / L) and 5 mL of tetraethyl orthosilicate in sequence, stir for 24 h, the solution color changes from dark black to light gray, indicating that SiO2 coating is successful, then add 1.88 mL of PFDTMS precursor solution (PFDTMS: EtOH = 5 mL: 100 mL) and keep stirring for 30 min, then slowly add 5 mL of H2SO4 aqueous solution (0.65 mol / L), continue stirring for 15 min, so that the carbon fluoride molecules can fully modify the surface of SiO2; then add 5.0 mL of hexamethyldisilazane (HMDS) to the obtained reaction system, continue stirring for 12 h, and obtain a photothermal composite super-amphiphobic topcoat;

[0080] (3) Under magnetic stirring conditions, 18 g of hydroxy acrylic resin, 3 g of fluorocarbon resin, 10 g of alkyd resin, 2.5 g of polypropylene resin, 0.6 mL of KH550 solution (KH550:H2O=0.24 mL:0.36 mL), 4 g of nylon powder, and 1 g of hexamethylene diisocyanate curing agent were added to 60 mL of butyl acetate in sequence, and stirred for 24 hours to obtain a modified resin primer;

[0081] (4) Spraying the resin primer obtained in (3) on the surface of the substrate, using a spray gun with a nozzle diameter of 1.5 mm and a pressure of 2.0-2.5 bar, and the distance from the nozzle to the substrate surface is 15-20 cm; after the primer is dry, spray the CuS enhanced photothermal composite super amphiphobic topcoat obtained in step (2), and air dry naturally to obtain the CuS enhanced photothermal super amphiphobic anti-icing coating, and the final coating thickness is about 300 to 500 μm.

[0082] Figure 1 , 2 The optical photographs of the coating samples obtained in this embodiment and the water contact angles and oil (edible oil) contact angles are respectively shown. The results show that the aqueous solution droplets of methyl blue can "stand" well on the coating surface, and the water contact angle is measured to be 159°; the oil droplets can also "stand" well on the coating surface, and the water contact angle is measured to be 155°; the obtained coating samples exhibit good superhydrophobic and superoleophobic properties.

[0083] Figure 3The transmission electron microscope (TEM) image of the CuS-Fe3O4 precipitate obtained in this example shows that the CuS nanoparticles are relatively small in size, while the Fe3O4 micromorphology is uniform spherical particles with a particle size of about 400 to 500 nm. The micromorphology of the formed composite particles is that the spherical Fe3O4 particles are surrounded by snowflake-shaped CuS small particles, and the Fe3O4 particles are uniformly distributed in the CuS nanoparticles.

[0084] Figure 4 This is a scanning electron microscope (SEM) image of the coating sample obtained in this embodiment, and the obtained coating has a micro-nano hierarchical structure: the super-amphiphobic photothermal composite super-liquid-repellent topcoat obtained by the present invention is deposited on the surface of the resin primer, and the surface of the obtained anti-icing coating exhibits micron-scale protruding composite deposits, and the particle size of the micron-scale protruding composite deposits is approximately between 30 and 60 μm (as shown in Figures a and b), which is mainly composed of CuS-Fe3O4@SiO2 composite nanoparticles and nanoscale SiO2 particles, and the surface of a single protrusion exhibits a layered rough structure (as shown in Figure c).

[0085] The present invention combines the surface modification of low surface energy materials with micro-nano structures and other means to construct a micro-nano rough structure that enables the CuS-Fe3O4@SiO2 anti-icing coating to have excellent super-amphiphobicity and wear and weather resistance.

[0086] Example 2

[0087] A CuS enhanced super-amphiphobic photothermal anti-icing coating, the preparation method of which comprises the following steps:

[0088] (1) Preparation of CuS-Fe3O4 composite materials:

[0089] Weigh 0.10 g Cu(Ac)2·H2O (0.05 mmol) and dissolve it in 12.5 mL deionized water to obtain a light blue Cu 2+ Precursor solution (0.04 M);

[0090] Weigh 1.25 mL of MPA (3-mercaptopropionic acid) solution (0.5 M, solvent is water) and add 0.2 g of commercially available Fe3O4 nanoparticles (particle size is 400-500 nm) into the MPA solution, and stir for 30 min to fully activate the surface of the Fe3O4 particles in the MPA solution;

[0091] Weigh 0.24 g Na2S·9H2O (1 mmol, S:Cu=2:1) ​​and dissolve it in 3 mL deionized water to obtain a colorless and transparent sulfur source solution (0.32 M), and add the obtained MPA solution to the sulfur source solution and stir evenly to obtain a S-Fe3O4-MPA precursor solution;

[0092] Under mechanical stirring conditions, the obtained S-Fe3O4-MPA precursor solution was slowly added to the obtained Cu at a drop rate of 100 drops / min. 2+ Precursor solution; after stirring at room temperature for 4 hours, a CuS-Fe3O4 black-green solution was obtained, which was washed with water and then centrifuged with ethanol to obtain a CuS-Fe3O4 precipitate;

[0093] (2) Under stirring, add 0.3 g of CuS-Fe3O4 precipitate obtained in step (1) to 25 mL of ethanol solvent and stir for 10 min, then add 1.5 mL of NaOH solution (1.8 mol / L) and 5 mL of tetraethyl orthosilicate in sequence and stir for 24 h; the color of the solution changes from dark black to light gray, indicating that the SiO2 coating is successful, then add 1.88 mL of PFDTMS precursor solution (PFDTMS:EtOH=5 mL:100 mL) and keep stirring for 30 min, then slowly add 5 mL of H2SO4 aqueous solution (0.65 mol / L) and continue stirring for 15 min to allow the carbon fluoride molecules to fully chemically modify the surface of the SiO2 particles; add 5.0 mL of hexamethyldisilazane (HMDS) to the resulting reaction system and continue stirring for 12 h to obtain a photothermal composite super-amphiphobic topcoat;

[0094] (3) Under magnetic stirring conditions, 18 g of hydroxy acrylic resin, 3 g of fluorocarbon resin, 10 g of alkyd resin, 2.5 g of polypropylene resin, 0.6 mL of kh550 solution (KH550: H2O = 0.24 mL: 0.36 mL), 4 g of nylon powder, and 1 g of hexamethylene diisocyanate curing agent were added to 60 mL of butyl acetate in sequence, and stirred for 24 hours to obtain a modified resin primer;

[0095] (4) Spraying the resin primer obtained in (3) on the surface of the substrate, using a spray gun with a nozzle diameter of 1.5 mm and a pressure of 2.0-2.5 bar, and the distance from the nozzle to the substrate surface is 15-20 cm; after the primer is dry, spray the CuS enhanced photothermal composite super amphiphobic topcoat obtained in step (2), and air dry naturally to obtain the CuS enhanced photothermal super amphiphobic anti-icing coating, and the final coating thickness is about 300 to 500 μm.

[0096] Figure 5 , 6 The optical photographs of the coating samples obtained in this embodiment and the photographs of the water contact angle and the oil (edible oil) contact angle are respectively shown. The results show that the aqueous solution droplets of methyl blue can "stand" well on the coating surface, and the water contact angle is measured to be 160°; the oil droplets can also "stand" well on the coating surface, and the water contact angle is measured to be 154°; the obtained coating samples show good super amphiphobic properties.

[0097] Figure 7The UV-visible absorption spectrum of the CuS enhanced photothermal composite super-liquid-repellent topcoat solution obtained in Examples 1 and 2 shows that the sample has a strong absorption peak in the near-infrared (with peaks at 350nm, 600nm, and 1200nm), and with the increase of the CuS content in the photothermal composite particles (the CuS content in Example 1 is higher than that in Example 2), the peak value of the main absorption peak also becomes larger, which indicates that the CuS-Fe3O4@SiO2 anti-icing topcoat coating synthesized by introducing CuS, an excellent photothermal nanoparticle, has a synergistically enhanced photothermal effect.

[0098] Comparative Example 1

[0099] A super-amphiphobic anti-icing coating, the preparation method of which comprises the following steps:

[0100] (1) Under magnetic stirring conditions, 1.5 mL of NaOH solution (1.8 mol / L) and 5 mL of ethyl orthosilicate were added to 25 mL of ethanol in sequence and stirred for 24 h;

[0101] (2) Add 1.88 mL of PFDTMS precursor solution (PFDTMS: EtOH = 5 mL: 100 mL) to the solution system obtained in step (1) and keep stirring for 30 min, then slowly add 5 mL of H2SO4 aqueous solution (0.65 mol / L) and continue stirring for 15 min;

[0102] (3) adding 5 mL of hexamethyldisilazane to the solution system obtained in step (2), and continuing stirring for 12 h to obtain a SiO2 super-amphiphobic topcoat;

[0103] (4) Under stirring conditions, 18 g of hydroxy acrylic resin, 3 g of fluorocarbon resin, 10 g of alkyd resin, 2.5 g of polypropylene resin, 0.6 mL of kh550 solution (KH550: H2O = 0.24 mL: 0.36 mL), 4 g of nylon powder, and 1 g of hexamethylene diisocyanate were added to 60 mL of butyl acetate in sequence, and stirred for 24 hours to obtain a resin primer;

[0104] (5) On the surface of the glass substrate, first spray the resin primer obtained in step 4) as a binder to improve the wear resistance and weather resistance of the coating. When spraying, use a spray gun with a nozzle diameter of 1.5 mm and a pressure of 2.0-2.5 bar, and the distance from the nozzle to the substrate surface is 15-20 cm; wait until the primer is dry; then when the primer is dry, spray the SiO2 super amphiphobic topcoat obtained in step 3) and dry to obtain a SiO2 super amphiphobic anti-icing coating. The final coating thickness is about 300 to 500 μm.

[0105] Comparative Example 2

[0106] A Fe3O4 photothermal super-amphiphobic anti-icing coating, the preparation method of which comprises the following steps:

[0107] (1) 0.2 g of commercially available Fe3O4 nanoparticles (particle size 400-500 nm) were dispersed in 50 mL of deionized water, sonicated for 30 min, and then centrifuged to dry;

[0108] (2) Under mechanical stirring conditions, Fe3O4 nanoparticles were added to 25 mL of ethanol, and then 1.5 mL of NaOH solution (1.8 mol / L) and 5 mL of ethyl orthosilicate were added in sequence, and stirred for 24 h;

[0109] (3) Add 1.88 mL of PFDTMS precursor solution (PFDTMS: EtOH = 5 mL: 100 mL) to the system obtained in step 2) and keep stirring for 30 min, then slowly add 5 mL of H2SO4 aqueous solution (0.65 mol / L) and continue stirring for 15 min;

[0110] (4) Add 5 mL of hexamethyldisilazane to the solution system obtained in step 3) and continue stirring for 12 h to obtain a Fe3O4 photothermal super-amphiphobic topcoat;

[0111] (5) Under magnetic stirring conditions, 18 g of hydroxy acrylic resin, 3 g of fluorocarbon resin, 10 g of alkyd resin, 2.5 g of polypropylene resin, 0.6 mL of kh550 solution (KH550: H2O = 0.24 mL: 0.36 mL), 4 g of nylon powder, and 1 g of hexamethylene diisocyanate curing agent were added to 60 mL of butyl acetate in sequence, and stirred for 24 hours to obtain a resin primer;

[0112] (6) On the surface of the glass substrate, first spray the resin primer obtained in step 5) as a binder to improve the wear resistance and weather resistance of the coating. When spraying, use a spray gun with a nozzle diameter of 1.5 mm and a pressure of 2.0-2.5 bar, and the distance from the nozzle to the substrate surface is 15-20 cm; after the primer is dry, spray the Fe3O4 photothermal super amphiphilic topcoat obtained in step 4) and dry it to obtain the Fe3O4 photothermal super amphiphilic anti-icing coating. The final coating thickness is about 300 to 500 μm.

[0113] Comparative Example 3

[0114] A CuS-Fe3O4 photothermal super-amphiphobic anti-icing coating, the preparation method of which comprises the following steps:

[0115] (1) Preparation of CuS-Fe3O4 materials:

[0116] Weigh 0.20 g Cu(Ac)2·H2O (1 mmol) and dissolve it in 25 mL deionized water to obtain a light blue Cu 2+ Precursor solution (0.04M),

[0117] Weigh 0.48 g Na2S·9H2O (2 mmol, S:Cu=2:1) ​​and dissolve it in 6.25 mL deionized water to obtain a colorless and transparent sulfur source solution (0.32 M);

[0118] Under mechanical stirring, slowly add the sulfur source solution to the Cu 2+ Precursor solution; after stirring for several hours at room temperature, a CuS black-green solution was obtained, which was washed with water and then centrifuged with ethanol to obtain a CuS black-green precipitate;

[0119] Take 0.2 g of commercially available Fe3O4 nanoparticles (particle size of 400-500 nm), add the Fe3O4 nanoparticles and the obtained CuS precipitate into 50 mL of deionized water, disperse them evenly, and centrifuge to dry to obtain a CuS-Fe3O4 precipitate;

[0120] (2) Under magnetic stirring, add 1.5 mL of NaOH solution (1.8 mol / L) and 5 mL of tetraethyl orthosilicate to 25 mL of ethanol in sequence and stir for 24 h; add 1.88 mL of PFDTMS precursor solution (PFDTMS:EtOH=5 mL:100 mL) and keep stirring for 30 min, then slowly add 5 mL of H2SO4 aqueous solution (0.65 mol / L) and continue stirring for 15 min; then add 5 mL of hexamethyldisilazane to the system and stir for 12 h to obtain a SiO2 super-amphiphobic dispersion;

[0121] (3) Under mechanical stirring, add 0.4 g of the CuS-Fe3O4 precipitate obtained in step (1) to the SiO2 super-amphiphobic dispersion obtained in step (2), and stir for 1 to 2 hours to obtain a CuS-Fe3O4 photothermal super-amphiphobic topcoat;

[0122] (4) Under magnetic stirring conditions, 18 g of hydroxy acrylic resin, 3 g of fluorocarbon resin, 10 g of alkyd resin, 2.5 g of polypropylene resin, 0.6 mL of kh550 solution (KH550: H2O = 0.24 mL: 0.36 mL), 4 g of nylon powder, and 1 g of hexamethylene diisocyanate curing agent were added to 60 mL of butyl acetate in sequence, and stirred for 24 hours to obtain a modified resin primer;

[0123] (5) Spray the resin primer obtained in step (4) on the surface of the substrate, using a spray gun with a nozzle diameter of 1.5 mm and a pressure of 2.0-2.5 bar, and the distance from the nozzle to the substrate surface is 15-20 cm. After the primer is dry, spray the CuS enhanced photothermal composite super liquid-repellent topcoat obtained in step (3) and air dry naturally to obtain the CuS-Fe3O4 photothermal super double-repellent anti-icing coating, and the final coating thickness is about 300 to 500 μm.

[0124] Comparative Example 4

[0125] A CuS-Fe3O4 super-amphiphobic photothermal anti-icing coating, the preparation method of which comprises the following steps:

[0126] (1) Preparation of CuS-Fe3O4 materials:

[0127] Weigh 0.20 g Cu(Ac)2·H2O (1 mmol) and dissolve it in 25 mL deionized water to obtain a light blue Cu 2+ Precursor solution (0.04 M);

[0128] Weigh 0.48 g Na2S·9H2O (2 mmol, S:Cu=2:1) ​​and dissolve it in 6.25 mL deionized water to obtain a colorless and transparent sulfur source solution (0.32 M);

[0129] Weigh 0.2 g of commercially available Fe3O4 nanoparticles (particle size of 400-500 nm), add them to the sulfur source solution and stir evenly to obtain a S-Fe3O4 precursor solution;

[0130] Under stirring conditions, the obtained S-Fe3O4 precursor solution was slowly added to the obtained Cu at a drop rate of 100 drops / min. 2+ Precursor solution; after stirring at room temperature for 4 hours, a CuS-Fe3O4 black-green solution was obtained, which was washed with water and then centrifuged with ethanol to obtain a CuS-Fe3O4 precipitate;

[0131] (2) Under stirring, add 0.4 g of CuS-Fe3O4 precipitate obtained in step (1) to 25 mL of ethanol solvent and stir for 10 min, then add 1.5 mL of NaOH solution (1.8 mol / L) and 5 mL of tetraethyl orthosilicate in sequence, stir for 24 h, and the color of the solution changes from dark black to light gray; add 1.88 mL of PFDTMS precursor solution (PFDTMS:EtOH=5 mL:100 mL) and keep stirring for 30 min, then slowly add 5 mL of H2SO4 aqueous solution (0.65 mol / L), continue stirring for 15 min, so that the carbon fluoride molecules can fully modify the surface of SiO2; then add 5.0 mL of hexamethyldisilazane (HMDS) to the obtained reaction system, continue stirring for 12 h, and obtain a photothermal composite super-amphiphobic topcoat;

[0132] (3) Under magnetic stirring conditions, 18 g of hydroxy acrylic resin, 3 g of fluorocarbon resin, 10 g of alkyd resin, 2.5 g of polypropylene resin, 0.6 mL of KH550 solution (KH550:H2O=0.24 mL:0.36 mL), 4 g of nylon powder, and 1 g of hexamethylene diisocyanate curing agent were added to 60 mL of butyl acetate in sequence, and stirred for 24 hours to obtain a modified resin primer;

[0133] (4) Spray the resin primer obtained in (3) on the surface of the substrate, using a spray gun with a nozzle diameter of 1.5 mm and a pressure of 2.0-2.5 bar, and the distance from the nozzle to the substrate surface is 15-20 cm; after the primer is dry, spray the CuS enhanced photothermal composite super liquid-repellent topcoat obtained in step (2), and air dry it naturally to obtain a photothermal super double-repellent anti-icing coating, and the final coating thickness is about 300 to 500 μm.

[0134] The coatings obtained in Examples 1 to 2 and Comparative Examples 1 to 4 were tested for super-amphiphobicity, anti-icing, stability and durability, and the specific test methods and results are as follows:

[0135] 1) Super amphiphobicity;

[0136] The water contact angle, water rolling angle, oil contact angle, and oil rolling angle of the six anti-icing coatings obtained in Example 1, Example 2, and Comparative Examples 1 to 4 were tested respectively, and the superamphiphobicity of the five coatings was compared.

[0137] 2) Photothermal heating performance

[0138] The six anti-icing coatings obtained in Example 1, Example 2, and Comparative Examples 1 to 4 were tested at 1 kW / m 2 The surface temperature rise after 5 minutes of illumination at different light intensity is compared to compare the photothermal heating performance of the six coatings.

[0139] 3) Delayed freezing performance in the absence of light

[0140] The delayed freezing time of the six anti-icing coatings obtained in the above-mentioned Example 1, Example 2, and Comparative Examples 1 to 4 was tested at the same temperature (-30° C.) and without light, and the specific steps were as follows:

[0141] Six glass sheets with a size of (5 cm × 5 cm × 0.3 cm) were prepared, and the six anti-icing coatings described in Example 1, Example 2, and Comparative Examples 1 to 4 were respectively coated on the surface of the glass sheets. A spray gun with a nozzle diameter of 1.5 mm and a pressure of 2.5 bar was used for spraying. The distance from the nozzle to the substrate surface was 15-20 cm. First, 3 mL of primer was sprayed on the surface of each glass sheet. After the primer was dry, 6 mL of super amphiphobic topcoat was sprayed.

[0142] After the coatings are completely dry, each coating is placed on a condensation table with an ambient temperature of -30°C. When the surface temperature of the coatings drops steadily to -30°C, 60 μL of methyl blue droplets are added, and then timing is immediately performed to record the time it takes for the droplets to completely freeze on each coating.

[0143] 4) Delayed freezing performance under light

[0144] The six anti-icing coatings obtained in Example 1, Example 2, and Comparative Examples 1 to 4 were tested at the same temperature (-30°C), 1kW / m 2 To delay the freezing time, the specific steps are as follows:

[0145] Six glass sheets (5 cm×5 cm×0.3 cm) coated with the six anti-icing coatings described in Example 1, Example 2, and Comparative Examples 1 to 4 were prepared, and the preparation method was the same as the above test method 3);

[0146] First, each anti-icing coating was placed on a condensation table with an ambient temperature of -30°C. When the surface temperature of the glass sheet stabilized to -30°C, 60 μL of methyl blue dye solution was added. Then, the xenon lamp was turned on and the light intensity was increased to 1 kW / m 2 Then start irradiating the coating surface and start timing, recording the time it takes for the droplets to completely freeze on each coating.

[0147] 5) De-icing time

[0148] The six anti-icing coatings obtained in Example 1, Example 2, and Comparative Examples 1 to 4 were tested at the same temperature (-15°C), 1kW / m 2 The specific steps for de-icing time are as follows:

[0149] Six glass sheets (5 cm×5 cm×0.3 cm) coated with the six anti-icing coatings described in Example 1, Example 2, and Comparative Examples 1 to 4 were prepared, and the preparation method was the same as the above test method 3);

[0150] First, each anti-icing coating was placed on a condensation table with an ambient temperature of -15°C. When the glass pieces were completely cooled to -15°C and adhered to the condensation table, the same volume (S×h=7.065cm 2 ×3cm) cylindrical mold, add an equal amount of water (30mL) into the mold, place it on a condensation table and freeze for a few hours. After ensuring that the two glass pieces are attached with icicles of the same shape and volume, lift the condensation table so that the coating and the condensation table are both at a 30° inclination with the horizontal plane. Then turn on the xenon lamp and increase the light intensity to 1kW / m 2 Then start irradiation and timing, and record the time when the icicles fall off the coating surface.

[0151] 6) Ice melting effect

[0152] The six anti-icing coatings obtained in Example 1, Example 2, and Comparative Examples 1 to 4 were tested at the same temperature (-20°C), 1kW / m 2 To achieve the ice melting effect, the specific steps are as follows:

[0153] Six glass sheets (5 cm×5 cm×0.3 cm) coated with the six anti-icing coatings described in Example 1, Example 2, and Comparative Examples 1 to 4 were prepared using the same preparation method as the above test method 3); and sufficient smoothies were prepared in the refrigerator for later use.

[0154] First, each anti-icing coating was placed on a condensation table with an ambient temperature of -20°C. When the glass sheet was completely cooled to -20°C and adhered to the condensation table, the condensation table was lifted so that both the coating and the condensation table were tilted at 5° to the horizontal plane. Then, an equal amount of ice cream was spread on the surface of the coating. Then, the xenon lamp was turned on and the light intensity was increased to 1kW / m 2 Then start irradiation and timing, record the time when all the ice melts into water and the water completely rolls off and leaves the coating surface.

[0155] 7) Chemical stability

[0156] The chemical stabilities of the six anti-icing coatings obtained in Example 1, Example 2, and Comparative Examples 1 to 4 were tested respectively: the six coatings were immersed in strong acid (HCl solution with pH = 1), strong base (NaOH solution with pH = 14) and salt water (NaCl solution with pH = 7) for several hours, and the samples were taken out every 12 hours and slowly rinsed with distilled water and dried. The water contact angle of each coating was tested, and the time when the coating lost its superhydrophobicity was observed.

[0157] 8) Wear resistance

[0158] The friction resistance of the six anti-icing coatings obtained in Example 1, Example 2, and Comparative Examples 1 to 4 was tested respectively: a glass slide (7.5 cm×2.5 cm×0.2 cm) of each coating was placed under a load of 100 g at a constant slow speed (about 1 cm s -1 ) was moved back and forth on sandpaper (800 mesh), and 20 cm was recorded as one wear cycle. After 500 wear cycles, the contact angle of each coating and the 2 Surface temperature rise after 5 minutes of exposure under xenon lamp conditions.

[0159] 9) Cyclic stability of photothermal heating

[0160] The light-heat heating performance of the six anti-icing coatings obtained in Example 1, Example 2, and Comparative Examples 1 to 4 were tested to see whether they had cyclic stability. The specific steps were as follows:

[0161] Each coated glass slide (7.5 cm × 2.5 cm × 0.2 cm) was placed in an oven and heated at 80 ° C for 2 h. After natural temperature recovery, it was placed in a -25 ° C refrigerator for 2 h as a hot and cold cycle. After five cycles, the contact angles of the six coatings and the contact angles at 1 kW / m 2 Surface temperature rise after 5 minutes of exposure under xenon lamp conditions.

[0162] 10) Durability

[0163] The durability of the six anti-icing coatings obtained in Example 1, Example 2, and Comparative Examples 1 to 4 was tested respectively: each coating was exposed outdoors for 90 days and then observed to see whether the coating appearance and water-oil contact angle showed obvious changes.

[0164] 11) Self-cleaning

[0165] The durability of the six anti-icing coatings obtained in Example 1, Example 2, and Comparative Examples 1 to 4 were tested respectively: the coating was contaminated with a hydrophilic solid pollutant (NaCl particles); after the coating was kept at a 5° inclination angle with the horizontal plane, 100 μL of methyl blue droplets were dropped on the top of the coating, and the droplets were allowed to fall naturally on the horizontal plane outside the coating to study the self-cleaning performance of the coating.

[0166] The corresponding test results of the anti-icing coatings obtained in Example 1, Example 2, and Comparative Examples 1 to 4 according to the above method are shown in Table 1 respectively.

[0167] Table 1 Comparative results of performance tests of anti-icing coatings prepared in Examples 1 to 2 and Comparative Examples 1 to 4

[0168]

[0169]

[0170] It can be seen from the above results that the composite anti-icing coating obtained in the present invention has excellent superhydrophobicity, superoleophobicity and photothermal conversion performance, and also exhibits good self-cleaning, resistance to cold and hot cycles, friction resistance, weather resistance and durability in actual application.

[0171] The present invention is not limited to the above-mentioned embodiments. For ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications are also considered to be within the scope of protection of the present invention. The contents not described in detail in this specification belong to the prior art known to professional and technical personnel in this field.

Claims

1. A CuS enhanced super-amphiphobic photothermal anti-icing coating, characterized in that: The invention comprises a photothermal composite super-amphiphobic surface layer and a resin bottom layer. In the topcoat used for the photothermal composite super-amphiphobic surface layer, each component and its weight proportion include: 0.06-0.08 parts of CuS-Fe3O4 composite material, 0.8-2 parts of hydrolyzable silicon source, 4-6 parts of alcohol solvent, 0.2-0.5 parts of alkali solution, 0.014-0.02 parts of fluorocarbon, 0.8-2 parts of acid solution and 0.8-2 parts of silane low surface energy material.

2. The CuS enhanced super dual photophobic and thermal anti-icing coating according to claim 1, characterized in that: The CuS-Fe3O4 composite material is firstly obtained by using a ligand to activate the surface of Fe3O4 particles, and then sequentially introducing a sulfur source and a copper salt for stirring reaction.

3. The CuS enhanced super dual photophobic and thermal anti-icing coating according to claim 2, characterized in that: The ligand is one of thioglycolic acid, 3-mercaptopropionic acid and glutathione.

4. The CuS enhanced super dual photophobic and thermal anti-icing coating according to claim 2, characterized in that: The sulfur source is one of sodium sulfide and thiourea; the copper salt is one or more of copper nitrate, copper acetate and copper chloride.

5. The CuS enhanced super dual photophobic and thermal anti-icing coating according to claim 2, characterized in that: The molar ratio of the introduced ligand, sulfur source and Fe3O4 particles is (0.5-1):(1-2):0.

86.

6. The CuS enhanced super dual photophobic and thermal anti-icing coating according to claim 1, characterized in that: The hydrolyzable silicon source is at least one of tetraethyl orthosilicate, methyltrimethoxysilane, ethyltriethoxysilane, tetramethylsiloxane, and sodium silicate; the fluorocarbon is at least one of perfluorodecyltrimethoxysilane, perfluorodecyltriethoxysilane, perfluorooctyltrimethoxysilane, and perfluorooctyltriethoxysilane.

7. The CuS enhanced super dual photophobic and thermal anti-icing coating according to claim 1, characterized in that: The silane-based low surface energy substance is one of hexamethyldisilazane, methyltriethoxysilane and hexadecyltrimethoxysilane.

8. The CuS enhanced super dual photophobic and thermal anti-icing coating according to claim 1, characterized in that: The components and their weight proportions in the primer used in the resin bottom layer include: 145-180 parts of resin matrix, 10-20 parts of powder filler, 4-5 parts of curing agent, 1.1-4 parts of silane coupling agent, and 240-300 parts of organic solvent.

9. The method for preparing the CuS enhanced super-amphiphobic photothermal anti-icing coating according to claim 1, characterized in that: The steps include: (1) Under stirring conditions, a CuS-Fe3O4 composite material is added to an alcohol solvent, and then an alkali solution and a hydrolyzable silicon source are sequentially added to the resulting mixed solution for hydrolysis reaction; a fluorocarbon-based precursor solution is added to perform a first stirring reaction, and then an acid solution is added to perform a second stirring reaction, and then a silane-based low surface energy material is added for stirring treatment to obtain a photothermal composite super-amphiphobic topcoat; (2) adding a resin matrix, a silane coupling agent, a powder filler, and a curing agent to an organic solvent in sequence under stirring, and stirring the mixture sufficiently to obtain a resin primer; (3) First spray the obtained resin primer on the surface of the substrate, and after the surface is dried, spray the obtained photothermal composite super-amphiphobic topcoat, and dry it to obtain the CuS enhanced super-amphiphobic photothermal anti-icing coating.

10. Use of the CuS enhanced super-amphiphobic photothermal anti-icing coating according to any one of claims 1 to 8 or the CuS enhanced super-amphiphobic photothermal anti-icing coating obtained by the preparation method according to claim 9.

Citation Information

Cited By

  • Wear-resistant anti-icing easily-deicing coating for power equipment and preparation method of wear-resistant anti-icing easily-deicing coating

    CN121801438A